PENGARUH CAMPUR KODE DALAM BAHASA INDONESIA DI KALANGAN MAHASISWA IKIP SILIWANGI BANDUNG - Suci Lestari; Syanti Oktaviani; Indra Permana (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This study aims to determine the effect of mixed use of code in the Indonesian language among students IKIP Siliwangi Bandung. Language is an arbitrary and universal symbolism system of sound. The use of the first language is closely related to the conscious and natural acquisition of language. Without someone aware of the use of code mix is often in use while learning a second language. The method used is descriptive qualitative method, sampling of this research is Indonesian language education student IKIP Siliwangi by limiting 25 students of IKIP Siliwangi. The instrument used is a questionnaire created by google form. The method of this study shows that there is a significant influence on the use of language denied students IKIP Siliwangi Bandung. This research is expected to provide an overview to all parties involved so that it can improve the way of using the language appropriate for use in any situation.